FLESHED VIEW, GEOGRAPHIES IN LIFE-FORMS - Marandola Jr., Eduardo (2018)
If Geography response the need of rethinking itself as contemporary challenge, like a self-critical task on it is role in colonialism and in the processes of the negation and domination of it, it must have to confront of the your view with bodies and their uses. A Geography of the fleshed view emerges from the situated knowledge it focus to life-forms, in carnal fold of the sensitive and the politics.